Electrospun composite PLLA/Oyster shell scaffold enhances proliferation and osteogenic differentiation of stem cells. (July 2018) - Didekhani, Roghaieh; Sohrabi, Mahmoud Reza; Seyedjafari, Ehsan; Soleimani, Masoud; Hanaee-Ahvaz, Hana
Abstract: In bone tissue engineering, bioceramics are of the most widely used materials for treatment of bone defects clinically. The composites of bioceramic/polymer fibrous scaffolds have been designed and developed to fulfill the mechanical and biological requirements of the damaged tissue. In the present study, oyster shell (OS) as a bioceramic in combination with the biodegradable and biocompatible poly (l -lactide) has been used to prepare a new tissue-engineered composite. The morphology, porosity, water contact angle and mechanical properties of scaffolds were investigated. Mesenchymal stem cells were also cultured on fabricated scaffolds to evaluate their potential to support cell proliferation and osteogenic differentiation. The SEM results indicated that the electrospun scaffolds were nanostructured and the OS were oriented along the fiber axis. The tensile strength and also the increased surface hydrophilicity of scaffolds after plasma treatment were suitable for tissue engineering applications. MTT assay demonstrated that the fabricated scaffolds were capable of supporting stem cell attachment and proliferation. Biomineralization measurements demonstrated the enhanced osteogenic differentiation of stem cells on composite PLLA/OS scaffolds. Taken together, these scaffolds were shown to hold promising potential for the treatment of bone defects in vivo.